2018
DOI: 10.1136/annrheumdis-2018-213920
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in patients with adult-onset still’s disease refractory to glucocorticoid treatment: a randomised, double-blind, placebo-controlled phase III trial

Abstract: ObjectiveTo evaluate the efficacy and safety of tocilizumab, an interleukin-6 receptor antibody, in patients with adult-onset Still’s disease.MethodsIn this double-blind, randomised, placebo-controlled phase III trial, 27 patients with adult-onset Still’s disease refractory to glucocorticoids were randomised to tocilizumab at a dose of 8 mg/kg or placebo given intravenously every 2 weeks during the 12-week, double-blind phase. Patients received open-label tocilizumab for 40 weeks subsequently. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 37 publications
(6 reference statements)
2
110
1
3
Order By: Relevance
“…The efficacy of these medications in AOSD is controversial, but some studies suggest that they have a place in the treatment of the chronic articular form [31][32][33], while others have showed rather disappointing results [19,20,34]. The excellent efficacy and clear steroid-sparing effect of tocilizumab determined in our study, concurring with the findings of a recent meta-analysis showing that AOSD patients treated with tocilizumab had a pooled remission rate of approximately 85% regardless of the phenotype [35], and of the first RCT investigating tocilizumab in AOSD [36], should make clinicians prioritize tocilizumab to anti-TNF blockers for patients with a chronic articular form of AOSD. Canakinumab showed some inconsistent results in AOSD [37][38][39] but is currently being investigated for its efficacy on AOSD's joint involvement (NCT02204293).…”
Section: Discussionsupporting
confidence: 89%
“…The efficacy of these medications in AOSD is controversial, but some studies suggest that they have a place in the treatment of the chronic articular form [31][32][33], while others have showed rather disappointing results [19,20,34]. The excellent efficacy and clear steroid-sparing effect of tocilizumab determined in our study, concurring with the findings of a recent meta-analysis showing that AOSD patients treated with tocilizumab had a pooled remission rate of approximately 85% regardless of the phenotype [35], and of the first RCT investigating tocilizumab in AOSD [36], should make clinicians prioritize tocilizumab to anti-TNF blockers for patients with a chronic articular form of AOSD. Canakinumab showed some inconsistent results in AOSD [37][38][39] but is currently being investigated for its efficacy on AOSD's joint involvement (NCT02204293).…”
Section: Discussionsupporting
confidence: 89%
“…AOSD and sJIA are increasingly considered to be the same disease, with AOSD occurring in adulthood and sJIA in childhood. In a double-blind RCT of 27 patients with AOSD refractory to treatment with glucocorticoids, an ACR50 response (reflecting 50% improvement) at week 4 was achieved in ~61% of patients treated with tocilizumab, compared with ~31% of placebo-treated patients, although the difference was not statistically significant 94 . Patients in the tocilizumab group also had improvements in systemic symptoms and a decreased dose of glucocorticoids compared with the placebo group.…”
Section: Il-6 Inhibition In Jia and Aosdmentioning
confidence: 94%
“…Tocilizumab is a humanized IgG1k monoclonal antibody which can specifically bind soluble or membrane-type IL-6 receptors (Sil-6R and Mil-6R), and has been widely used in the treatment of autoimmune diseases such as rheumatoid arthritis [58], adult-onset Still's disease [59], and large vessel vasculitis [60]. For COVID-19 infection, clinical studies have shown that serum levels of inflammatory mediators in severe patients are significantly higher than those in common patients [22].…”
Section: Tocilizumabmentioning
confidence: 99%